2015
DOI: 10.1017/s1742170514000441
|View full text |Cite
|
Sign up to set email alerts
|

Distance to slaughter, markets and feed sources used by small-scale food animal operations in the United States

Abstract: Distances to common production and marketing supply chain destinations may vary, and this has economic and animal health implications for small-scale food animal operations. Proximity to these destinations can affect the economic viability and marketing decisions of small-scale operations and may represent significant barriers to sustainability. Data were collected using a cross-sectional survey conducted by the US Department of Agriculture's (USDA) National Animal Health Monitoring System in 2011 using a stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…These animal distances fall within the range of travel distances found in the literature. For small livestock operations (representing 40% of total US farms), the 25th to 75th percentile range for poultry (12-60 miles) and pigs (25-180 miles) encompass our modeled results (58). The 25th to 75th percentile range for cattle was below our average at 15-40 miles; however, another study of 21 large feedlots found that cattle travel an average of 434 miles (59).…”
Section: Resultsmentioning
confidence: 47%
“…These animal distances fall within the range of travel distances found in the literature. For small livestock operations (representing 40% of total US farms), the 25th to 75th percentile range for poultry (12-60 miles) and pigs (25-180 miles) encompass our modeled results (58). The 25th to 75th percentile range for cattle was below our average at 15-40 miles; however, another study of 21 large feedlots found that cattle travel an average of 434 miles (59).…”
Section: Resultsmentioning
confidence: 47%
“…This estimate is reasonable when compared with the other recent studies. Beam et al (2015) estimated the average farm-slaughter facility for several cattle sectors in the USA. In the poultry industry, at the aggregate level the distance ranges from 2 to 250 miles with a median distance equal to 19 miles.…”
Section: Budget Assessmentmentioning
confidence: 99%
“…This is not a surprising model outcome and is consistent with previously published survey results, showing that the distance to the slaughterhouse was one of the most important factors to consider when establishing new operations and that most animal producers (95th percentile) transport animals (feedlot to slaughterhouse) to a maximum distance of 75 miles. 53 The above observations suggest that the county-level beef network might be a scale-free network. Scale-free networks are characterized by the presence of hubs, small diameter, resistance to random disruptions, and preferential attachment.…”
Section: Setsmentioning
confidence: 84%